2003
DOI: 10.1016/s0042-6989(03)00171-8
|View full text |Cite
|
Sign up to set email alerts
|

Configural information is processed differently in perception and recognition of faces

Abstract: Several previous studies have stressed the importance of processing configural information in face recognition. In this study the perception of configural information was investigated. Large overestimations were found when the eye-mouth distance and the inter-eye distance had to be estimated. Whereas configural processing is disrupted when inverted faces have to be recognized the perceptual overestimations persisted when faces were inverted. These results suggest that processing configural information is diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Rakover (1999) found that in certain cases, the inversion of Thatcherized and scrambled faces in which the configural relations were changed not only did not decrease the degree of strangeness of the faces, but it even increased it-a finding that does not accord with the configural-processing hypothesis (see also Bruyer, 2011). Schwaninger, Ryf, and Hofer (2003) found that the geometrical horizontal-vertical (H-V) illusion in a face resists inversion. (The H-V illusion refers to a visual form in the shape of a T in which the horizontal line is perceived as being shorter than the vertical line, although the two lines are of equal length.)…”
Section: A Necessary and A Sufficient Conditionmentioning
confidence: 99%
“…Rakover (1999) found that in certain cases, the inversion of Thatcherized and scrambled faces in which the configural relations were changed not only did not decrease the degree of strangeness of the faces, but it even increased it-a finding that does not accord with the configural-processing hypothesis (see also Bruyer, 2011). Schwaninger, Ryf, and Hofer (2003) found that the geometrical horizontal-vertical (H-V) illusion in a face resists inversion. (The H-V illusion refers to a visual form in the shape of a T in which the horizontal line is perceived as being shorter than the vertical line, although the two lines are of equal length.)…”
Section: A Necessary and A Sufficient Conditionmentioning
confidence: 99%
“…However, the work of Schwaninger, Ryf & Hofer (2003) demonstrated that whereas people are very sensitive in detecting configural differences, configural information is not perceived veridically, but is instead overestimated by 11-41 per cent. In fact, inversion strongly impairs configural processing in detection and recognition tasks, but the perception of configural information is much less orientation-sensitive (Schwaninger, Ryf & Hofer, 2003).…”
Section: Configural Processing In Childhoodmentioning
confidence: 99%
“…In fact, inversion strongly impairs configural processing in detection and recognition tasks, but the perception of configural information is much less orientation-sensitive (Schwaninger, Ryf & Hofer, 2003). Thus, the methodology used in different studies needs always to be considered when evaluating findings.…”
Section: Configural Processing In Childhoodmentioning
confidence: 99%
“…It is important to note that as spatial quantization eliminates information about the form of local features rather than about the mutual distances and directions between the approximate locations where these features (''feature tokens'') are situated, it should be considered as a transformation that impairs the fine-scale relational aspect of configurational processing (e.g., see Leder & Bruce, 2000;Schwaninger et al, 2003) rather than the coarse-scale wholistic aspect of configurational processing.…”
Section: Spatial Quantization and Maskingmentioning
confidence: 99%
“…But we do not directly manipulate basic configurational characteristics. This is a serious problem because configurational characteristics pertaining to inter-feature distances differently influence performance in higher-level face recognition and lower-level facial image perception tasks (Schwaninger, Ryf, & Hofer, 2003).…”
Section: Introductionmentioning
confidence: 99%